A Randomized Trial of the Topical Effect of Antifibrinolytic Epsilon Aminocaproic Acid on Coronary Artery Bypass Surgery Without Cardiopulmonary Bypass - Gurian, Danilo Bortolotto; Meneghini, Adriano; Abreu, Luiz Carlos de; Murad, Neif; Matos, Leandro Luongo de; Pires, Adilson Casemiro; Valenti, Vitor E. [UNESP]; Breda, Joao Roberto (Sage Publications Inc, 2014)
We assessed the effect of the topical application of epsilon-aminocaproic antifibrinolytic acid (EACA) on the pericardium of patients submitted to coronary artery bypass graft (CABG) without the use of cardiopulmonary bypass (CPB). This is a prospective, randomized, and double-blind study. We evaluated 26 patients with chronic coronary heart disease indicated for CABG without CPB (EACA and placebo groups). The analysis of the postoperative hematological results showed no difference between groups in hemoglobin and hematocrit. There was no difference between the groups regarding the postoperative bleeding through the drains in the first 24 hours, 48 hours, and accumulated loss until removal of drains. The use of EACA in patients undergoing CABG without CPB presented no difference in the reduction of the amount of bleeding and the need for blood transfusions.
Keywords: bypass; cardiopulmonary; coronary artery bypass; bypass surgery; coronary artery; antifibrinolytics